Death, materiality and mediation : an ethnography of remembrance in Ireland - Graham, Barbara, 1954- (Material mediations, 2017)
Barbara Graham analyzes a diverse range of objects associated with remembrance in both the public and private arenas through ethnography of communities on both sides of the Irish border. In doing so, she explores the materially mediated interactions between the living and the dead, revealing the physical, cognitive, emotional, and spiritual roles of the dead in contemporary communities. Through this study, Graham expands the concept of materiality to include narrative, song, senses, emotions, ephemera and embodied experience. She also examines how modern practices are informed by older beliefs and folk religion.